Glandular odontogenic cyst: Report of a pediatric case in an uncommon location - Asha V,; Nevica Baruah,; Saleha Jamadar, (Indian Journal of Case Reports, 2021)
Glandular odontogenic cyst (GOC), first described by Padayachee and Van Wyk in 1987, is a rare odontogenic cyst of the jaw which is commonly prevalent in the fourth decade. Clinically, it commonly presents as an asymptomatic swelling in the mandibular anterior region. A conclusive diagnosis can be given through histopathological examination. GOC is found to have a high recurrence potential which requires regular follow-up. Here, a rare case of a 14-year-old boy is described who presented with a swelling in left mandibular posterior teeth.